Interpreting Hope: A Critical Hermeneutic Study of Tourism Development Visibility, Justice, and Sustainability in North Sinjai District, Indonesia - Nur isra Resyah; Astariadi Kurniawan; Ainun; Yoshie Sukendar Anwar; Myrza Rahmanita (CV. Science Tech Group, 2025)
This study analyzes the May 2024 Indonesian Public Image Survey Report–LSI Denny JA in North Sinjai District, South Sulawesi, using a hermeneutic-critical approach based on Ricoeur and Habermas. The results show a complete absence of tourism (0.0%) from the narrative of community expectations, the lowest satisfaction with tourism management (63%), and the highest dissatisfaction with fishermen (44.8%). This phenomenon reflects chronic undertourism and the structural invisibility of tourism in the lifeworld of local communities. The paradox of high satisfaction (71.3%) amidst economic hardship (62.3%) provides a golden time window of 2025–2027. The study recommends a “Community First, Tourism Later” strategy with the empowerment of 1,000 fishing families, dual infrastructure, and a local-level INSTO-UNWTO pilot. North Sinjai has the potential to become a national model for transitioning from extreme undertourism to sustainable, inclusive and equitable micro-tourism.